Faktor Penyebab Komersialisasi Pendidikan - Alifiani Purwaningrum; Muhammad Rifa’i Subhi (Muaddib: Jurnal Pendidikan Agama Islam, 2023)
Commercializing education means turning education into a business or incorporating business elements into it. Of course, this often happens at various levels of education. Many schools collect fees outside of government regulations, or the government usually mentions extortion fees in schools, then the government blames the school, by linking the boss's funds. If in a formal education school, the school only relies on money from BOS funds, of course the school will experience passivity in carrying out learning activities. There are many new things related to supporting learning activities, which cannot be fulfilled, because they are hampered by the lack of BOS funds. It cannot be denied that formal education schools, which usually prioritize quality, are schools that usually have high fees, and only the well-off can afford the financing. In terms of formal education, of course there don't seem to be a few people who take advantage of this for business purposes, where the fees set are quite burdensome for parents of students, but again, schools always set rates according to the facilities provided, both from teachers and teachers. professional, complete learning support tools, comfortable buildings, and so on